2014
DOI: 10.1001/jamapediatrics.2013.4469
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Fever After Pediatric Trivalent Inactivated Influenza Vaccine and 13-Valent Pneumococcal Conjugate Vaccine

Abstract: clinicaltrials.gov Identifier: NCT01467934.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 21 publications
6
44
0
Order By: Relevance
“…A subsequent study of the 2011/12 US influenza season confirmed elevated fever after concurrent TIV and PCV13 on Day 0 to 1 and listed fever rates after TIV alone similar to our findings at 7.5% in children aged six to 23 months [68].…”
Section: Discussionsupporting
confidence: 88%
“…A subsequent study of the 2011/12 US influenza season confirmed elevated fever after concurrent TIV and PCV13 on Day 0 to 1 and listed fever rates after TIV alone similar to our findings at 7.5% in children aged six to 23 months [68].…”
Section: Discussionsupporting
confidence: 88%
“…Increasing evidence suggests that co-administration and type of vaccine co-administered could play a role in the occurrence of an event such as convulsions following PCV. Overall, the results of our study are coherent with available literature data [19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…This study showed a risk of febrile seizure when TIV was co-administered with PCV13 that was higher than after single administration of TIV or PCV13 [21]. These findings were validated by an observational study conducted in the US which used prospective data collection and showed a higher risk of fever when TIV and PCV13 were co-administered than when either of these vaccines was administered without the other [22]. Increasing evidence suggests that co-administration and type of vaccine co-administered could play a role in the occurrence of an event such as convulsions following PCV.…”
Section: Discussionsupporting
confidence: 66%
“…In Australia, SMS technology has also been used to study vaccine reactions among healthcare workers and pregnant women [13,14]. One study in the United States also used SMS follow-up of parents, detecting increased fever rates in children who had concomitantly received trivalent influenza vaccine and 13-valent pneumococcal vaccine compared with those who received each vaccine alone [15]. Similarly, we reported an increased (although low) rate of fever when influenza vaccine was administered together with other vaccines.…”
Section: Discussionsupporting
confidence: 58%